Ánh xạ cơ sở dữ liệu, các bài toán tách và cập nhật độc lập - Tich, Ho Van (Journal of Computer Science and Cybernetics, 2018)
In this paper, we apply the theory of data base mappings to the important areas of data base systems:  data base n-decomporition and independent update in distributed data base. We show how our general results reduced to well known results in the  special case of projection and functional dependencies.